Church teaching on marriage and family as an instruction for the state legislator in the context of Poland = L’enseignement de l’Église sur le mariage et la famille en tant qu’indice pour le législateur national dans le contexte de la Pologne = L’insegnamento della Chiesa sul matrimonio e la famiglia come guida per i legislatori statali polacchi - Kroczek, Piotr (Philosophy & canon law, 2015)
The Church has the right and duty “always and everywhere to proclaim moral principles, even in respect of the social order” (can. 747 § 2), and the faithful are “to ensure that their actions are permeated with the spirit of the Gospel, and they are to heed the teaching of the Church proposed by the magisterium” (can. 227). The 20th anniversary of the publication of the Letter to Families from Pope John Paul II Gratissimam Sane is a great opportunity to recall the document and to bring to light some thoughts on family that would be useful instructions for those who, in the context of Poland, are bearing the legislative power. The paper presents five important ideas on marriage and family that must be, from catholic point of view, in some way present in state law. The ideas concern: marriage as sovereign society, marriage as heterosexual union, the threats of gender ideology for the family, the proper relations between the parents and children, and the professional work and the work within the family unit.